Gryllus mandevillus (Orthoptera: Gryllidae) is a valid field cricket species - Weissman, David B.; Funk, David H.; Walker, Thomas J. (Zootaxa, 2012)
Walker (in Weissman, Walker, & Gray 2009) described a new species of Gryllus, G. jamaicensis, a second species recorded from Jamaica to the widespread G. assimilis (Fabricius 1775).   The two taxa are apparent sister species and are morphologically indistinguishable. They can be separated by three calling song characteristics: pulses per chirp, average pulse rate, and dominant frequency.